EPIDEMIOLOGY OF TRAFFIC ACCIDENTS IN TEHRAN II. AGENT: THE FAULTY DRIVERS - K Nasseri; A Sing; F Azordegen; A Nadim (Tehran University of Medical Sciences, 1977)
Of the 5,655 accidents with casualty that had occurred during 1973 in Teheran, 4,936 or 87. 3% were caused by the negligence on the part of the drivers. The most accident producing driving middle-aged men of 30- 39 years, who had recently acquired driving permit and were wage earners as drivers in the city of Tehran. Alcohol intoxication as the cause of the accident had been recorded in only o.12% of the cases. These and other results have been discussed.